Assessment of small mechanical wastewater treatment plants: Relative life cycle environmental impacts of construction and operations. (15th August 2021) - Moussavi, Sussan; Thompson, Matthew; Li, Shaobin; Dvorak, Bruce
Abstract: Many slow growing and shrinking rural communities struggle with aging or inadequate wastewater treatment plants (WWTPs), and face challenges in constructing and operating such facilities. Although existing literature has provided insight into the environmental sustainability of large facilities, including both the construction and operational phases, these studies have not examined small, rural facilities treating less than 7000 m 3 /d (1.8 MGD) of wastewater in adequate depth and breadth. In this study, a detailed inventory of the construction and operational data for 16 case studies of small WWTPs was developed to elucidate their environmental life cycle impacts. An attributional LCA framework was followed. The results show that the environmental impacts of both the construction and operational phases are considerable. Energy use was the dominant contributor to the operational environmental impact, and improving energy efficiency of a plant may reduce the environmental impacts of a small WWTP. Construction impacts can vary considerably between facilities (e.g., coefficient of variation for the construction impacts ranged from 60% to 78% depending on the impact category). Process-related factors (e.g., concrete and reinforcing steel used in basins) are typically sized using the design flow; thus, much of the variability in construction impacts among plants stems from the non-process related infrastructure. Multiple regression analysis was used as an exploratory tool to identify which non-process related plant aspects contribute to the variable environmental impact of small WWTPs. These factors include aluminum, cast iron, and the capacity utilization ratio (defined as the ratio of average flow to design flow). Thus, industry practitioners should consider these factors when aiming to reduce the environmental impacts of a small WWTP related to construction. Scenario sensitivity analyses found that the environmental impact of construction became smaller with longer design life, and the end-of-life consideration does not heavily influence the environmental sustainability of a WWTP. Graphical abstract: Image 1 Highlights: LCA was applied to evaluate environmental impacts of 16 case studies of small wastewater plants. Construction can be a large share of the total environmental impact of a small wastewater treatment plant. Multiple regression analysis was used to relate environmental impacts to inventory. Overdesign of small, slow-growing wastewater treatment plant infrastructure is discouraged. End-of-life considerations do not heavily influence the environmental impact.